Radiographic skeletal survey for non‐accidental injury: Systematic review and development of a national New Zealand protocol. Issue 1 (7th January 2015) - Phillips, Karin L.; Bastin, Sonja T.; Davies‐Payne, David; Browne, Diana; Bird, Helen L.; Craw, Susan; Duncan, David; Depree, Philippa; Leigh, Alina; McLaughlin, Andrew; Metcalfe, Russell; Murdoch, Jean; et al.
Abstract Introduction Clinically occult fractures from non‐accidental injury (NAI) are best detected on radiographic skeletal survey. However, there are regional variations regarding the views included in such surveys. We undertook a systematic review of the evidence supporting skeletal survey protocols to design a protocol that could be implemented across New Zealand. Methods In June 2013, we searched Medline, Google Scholar, the Cochrane database, UpToDate and relevant reference lists for English‐language publications on skeletal survey in NAI from 1946. We included publications that contained a protocol or reported evidence supporting including, or excluding, specific views in a skeletal survey. All included publications were critically appraised. Based on this systematic review, a draft protocol was developed and presented to an Australian and New Zealand Society for Paediatric Radiology NAI symposium in October 2013. Feedback from the symposium and later discussions was incorporated into the final protocol. Results We identified 2 guidelines for skeletal survey, 13 other protocols and 15 articles providing evidence for inclusion of specific images in a skeletal survey. The guidelines scored poorly on critical appraisal of several aspects of their methods. We found no studies that validate any of the protocols or compare their performance. Evidence supporting inclusion in a skeletal survey is limited to ribs, spine, pelvis, hands and feet, and long bone views. Our final protocol is a standardised, two‐tiered protocol consisting of between 17 and 22 views. Conclusion A standardised protocol for radiographic skeletal survey protocol has been developed in New Zealand. We present it here for consideration by others.